Ayurvedic Treatment of Acute Ischemic Stroke: A Prospective Observational Study - J Aarthi Harini BAMS; Avineet Luthra BPT, MSc; Shrey Madeka MSc; Prasan Shankar BAMS, MD (Ayu.); Pitchaiah Mandava MD, PhD, MSEE; Ravishankar Pervaje BAMS, MS (Ayu.); Sanjith Aaron MBBS, MD, DM; Archana Purushotham MD, PhD (SAGE Publishing, 2019)
Background The western medical arsenal for treating stroke is rather limited, and the only treatments shown to improve outcomes are not accessible to most in the third world. Even in the developed world, many patients present too late to receive thrombolysis or thrombectomy. Stroke patients in India commonly use Ayurvedic therapies, but there are no published data regarding the efficacy or safety of these therapies, the latter being of particular concern in acute ischemic stroke (AIS). Objective To obtain preliminary data on the safety and efficacy of stand-alone whole-system Ayurvedic treatment in AIS. Methods We present here an observational study prospectively comparing outcomes in 2 cohorts of AIS patients treated with whole-system classical Ayurveda (n = 13) or conservative (nonthrombolytic, noninterventional) western biomedicine (n = 20). Results Pooled analysis of outcomes did not show statistically significant differences in mortality (15.38% vs 15%, P  = 1.00), nonfatal adverse event rates (15.38% vs 30%, P  = .4), or functional disability measures. A paired analysis performed using a matching algorithm to reduce baseline disparities between the cohorts also showed no statistically significant differences in outcomes. Conclusions The safety profiles of classical Ayurveda and conservative western biomedicine in AIS are similar. This is the first ever report of stand-alone Ayurvedic therapy in AIS. Our results support the conduct of a randomized controlled trial to study the efficacy of Ayurvedic treatment of AIS.